KONTRIBUSI IBU RUMAH TANGGA PENJUAL IKAN TERHADAP PENDAPATAN KELUARGA DI KECAMATAN ABELI KOTA KENDARI - Wulan Ali Rahmin; La Nalefo; Suriana Suriana (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2022)
Contributions and the role of housewives are influential and very necessary to be able to support the household life of his family. This research aims: to increase income  Fish selling families in Abeli District, Kendari Besar City contribute to mother's income  fish selling households to family income in Abeli District, Kendari City  In August 2022, this research was conducted which is located in the District Lapulu market  Abeli, Kendari City. The research location was determined purposively (intentionally).  Respondents were 20 housewives who worked as fish sellers in the market.  This study uses a quantitative methods. The results of the study show the magnitude family income of a fish seller in the Lapulu Market, Abeli District, Kendari City as  following: a) Husband's work as a fisherman Rp. 8,565,674/month b) Husband's work  as a construction worker of IDR 7,831,648/month and c) The husband's job is as a farmer  IDR 4,408,207/month. The contribution of the fish selling housewife (fisherman's wife) is  by 79%, while the contribution of housewives selling fish (wife of a construction worker)  is equal to 73% and the contribution of housewives selling fish (farmer's wife) is equal to  81%. The biggest contribution of housewives is that of fish selling housewives  (farmer's wife) by 81%, while the contribution of housewives selling fish is the smallest  are housewives selling fish (wife of a construction worker) by 73%.